THE BATTLE AGAINST CYBERBULLYING: A DISCURSIVE ANALYSIS OF PUBLIC POLICIES IN BRASIL - Neide Aparecida Ribeiro; Geraldo Caliman (European Scientific Journal, ESJ, 2015)
This article analyses public policies about cyberbullying in Brazil starting with an Internet investigation about bills pending in National Congress, existent legislations and UNESCO’s recommendations. The goal is to verify, by means of critical discourse analysis, to whom these policies are destined, which are the predominant discourses and the values and intentions that they represent. The problem found is in the absence of specific public policies to the cyberbullying phenomenon due to subdivisions made to wide legislations and the influence of international agencies. To decrease violence that is produced by virtual bullying, strategies are suggested, such as inserting education as protagonist of public policies that may be implemented, taking into account the human rights paradigm as a fundamental value.